Luminescence property and large-scale production of ZnO nanowires by current heating deposition - P. Singjai (2018)
Large-scale production for ZnO nanowires has been demonstrated by current heating deposition. Based on the use of a solid-vapor phase carbothermal sublimation technique, a ZnO-graphite mixed rod was placed between two copper bars and gradually heated by passing current through it under constant flowing of argon gas at atmospheric pressure. The product seen as white films deposited on the rod surface was separated for further characterizations. The results have shown mainly comb-like structures of ZnO nanowires in diameter ranging from 50 to 200 nm and length up to several tens micrometers. From optical testing, ionoluminescence spectra of as-grown and annealed samples have shown high green emission intensities centered at 510 nm. In contrast, the small UV peak centered at 390 nm was observed clearly in the as-grown sample which almost disappeared after the annealing treatment. © 2006 Elsevier B.V. All rights reserved.